Rapid and visual detection of 2019 novel coronavirus (SARS-CoV-2) by a reverse transcription loop-mediated isothermal amplification assay. (June 2020) - Yan, C.; Cui, J.; Huang, L.; Du, B.; Chen, L.; Xue, G.; Li, S.; Zhang, W.; Zhao, L.; Sun, Y.; Yao, H.; Li, N.; et al.
Abstract: Objective: To evaluate a reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay for detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and compare it with RT-PCR. Methods: We designed primers specific to the orf1ab and S genes of SARS-CoV-2. Total viral RNA was extracted using the QIAamp Viral RNA Mini Kit. We optimized the RT-LAMP assay, and evaluated it for its sensitivity and specificity of detection using real-time turbidity monitoring and visual observation. Results: The primer sets orf1ab-4 and S-123 amplified the genes in the shortest times, the mean (±SD) times were 18 ± 1.32 min and 20 ± 1.80 min, respectively, and 63°C was the optimum reaction temperature. The sensitivities were 2 × 10 1 copies and 2 × 10 2 copies per reaction with primer sets orf1ab-4 and S-123, respectively. This assay showed no cross-reactivity with 60 other respiratory pathogens. To describe the availability of this method in clinical diagnosis, we collected 130 specimens from patients with clinically suspected SARS-CoV-2 infection. Among them, 58 were confirmed to be positive and 72 were negative by RT-LAMP. The sensitivity was 100% (95% CI 92.3%–100%), specificity 100% (95% CI 93.7%–100%). This assay detected SARS-CoV-2 in a mean (±SD) time of 26.28 ± 4.48 min and the results can be identified with visual observation. Conclusion: These results demonstrate that we developed a rapid, simple, specific and sensitive RT-LAMP assay for SARS-CoV-2 detection among clinical samples. It will be a powerful tool for SARS-CoV-2 identification, and for monitoring suspected patients, close contacts and high-risk groups.